2014
DOI: 10.1007/s11356-014-3198-8
|View full text |Cite|
|
Sign up to set email alerts
|

Chlorinated and brominated organic pollutants in shellfish from the Yellow Sea and East China Sea

Abstract: The global contamination with persistent organic pollutants (POPs), or compounds with similar characteristics, is well known. Still there are data gaps for POP concentrations from many areas in the world. The aim of the present study is to assess several legacies POPs and also hexabromocyclododecane (HBCDD) and methoxylated polybrominated diphenyl ethers (MeO-PBDEs) in shellfish from three locations in the Yellow Sea and East China Sea. The sources of the contaminants are discussed. Pooled samples were treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 45 publications
1
12
0
Order By: Relevance
“…Recent studies have indicated that dicofol may be the new source of DDTs in marine environment (Wong et al, 2005;Yin et al, 2015). Here, the indexes of (DDE + DDD) / DDTs (Qiu et al, 2005;Zhang et al, 2011;Da et al, 2014) have been used for studying source changes of DDTs in the SYS.…”
Section: Sources Of Ddtsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have indicated that dicofol may be the new source of DDTs in marine environment (Wong et al, 2005;Yin et al, 2015). Here, the indexes of (DDE + DDD) / DDTs (Qiu et al, 2005;Zhang et al, 2011;Da et al, 2014) have been used for studying source changes of DDTs in the SYS.…”
Section: Sources Of Ddtsmentioning
confidence: 99%
“…Although the Yellow River and Yangtze River do not directly discharge into the YS, large amounts of terrestrial materials from these two rivers have been deposited in the YS due to transports by ocean currents (Huh and Su, 1999;Lim et al, 2007). In addition, the coastal areas of the southern YS (SYS) are densely populated, and aquaculture is highly developed (Yin et al, 2015). As a result approximately 7.6% of contaminants from municipal and industrial activities around the SYS coastal regions have been discharged into the SYS (China's State Oceanic Administration (CSOA), 2007; Ministry of Environmental Protection of the People's Republic of China (MEPPRC), 2007; Duan et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Benthic invertebrates are considered as good indicator species for local environmental pollution since they have a wide geographic distribution and a low mobility (Goldberg et al 1978; Ramu et al 2007b). Mussels have been widely applied to investigate environmental contamination of POPs and heavy metal (Giandomenico et al 2013; Ramu et al 2007a; Yin et al 2015). However, in the Taihu Lake area, mussels are commonly cultivated for pearl production and the natural mussels are rarely found.…”
Section: Introductionmentioning
confidence: 99%
“…Especially, some persistent organic pollutants (pops) possess good chemical stability, high toxicity, and longevity in natural environment [1,2], which have caused many serious problems for human health. How to remove the pops through an efficient and economic method has become urgent.…”
Section: Introductionmentioning
confidence: 99%